Cross-age comparison of meanings and motives toward luxury consumption among Thai baby boomer and generation Y consumers - Viriyopas, Khanitha (2013)
The growth of luxury markets have been expanded worldwide since the past until today. It cannot be denied that Asian markets have been valuable markets for several global luxury brands as a significant rise in emerging markets of these Asian countries. Thailand has been one of them. With consequences of higher standard of living and more openness to globalisation trends, Thailand has become one of growing and profitable luxury market. These luxury brands have been attractive to various Thai consumer segments including younger to older consumers. Baby boomer consumers who have high purchasing power and generation Y consumers who tend to be easily motivated by luxury consumption marketing are considered as potential customers for Thai luxury market. However, luxury consumption behaviors of Thai consumers still relatively lacks of studies in this field as most related theories and empirical studies are focused on Western consumers and not specific on particular age segments. To examine perceived meanings and value toward luxury products and motives to luxury consumption is important among these two generations of Thai consumers would be beneficial for each luxury brand to formulate effective marketing strategies in order to gain competitive advantages in this valuable market. This study aims to fill this gap by investigating perceived meanings toward luxury products and what luxury value perceptions and significant motives influencing Thai baby boomer and generation Y consumers to purchase luxury products as well as examining similarities and differences of these findings. This study also develops new dimensions of luxury value perceptions models for these two generations. Quantitative method was applied to this study with 208 respondents from both generations. Five-Likert scales questionnaire was formed based on measurement scale items of previous studies in order to examine motives influencing luxury consumption. Factor analysis and reliable analysis were implemented to develop dimensions of luxury value perceptions models for Thai consumers from each generation. The results indicated that there is no significant difference of meanings toward luxury products as well as motives influencing intentions to luxury consumption of these two groups. They perceived luxury products as products with high quality and high price. Individual value and functional value of particular luxury products were critical motives contributing to their luxury product purchase. However, baby boomer group had higher level of certain types of value perceptions regarding social value, functional value and relational value when considering to buy luxury products.